Assessment of food security status among rural and urban households in Kuching district, Sarawak, Malaysia - Mohd Abu Bakar, Wan Azdie; Mphd Ramdzan, Ainnalina (2013)
Background and objectives: Food security can be defined as the availability of and accessibility to food, acquired in an acceptable means at any given time and place in a way that could maintain health and wellbeing. Research on food security in Malaysia is still in its infancy stage, and the extent of food security situation in Sarawak, a part of Borneo Island, remains unexplored. Methods: This cross-sectional study aimed to measure the prevalence of food insecurity and to examine the associations between food security status with demography, socioeconomic factors and coping strategies. A total of 127 mothers from low income households in Padawan and Petra Jaya areas in Kuching District, Sarawak were interviewed. Structured questionnaire was used to collect the data and information. The Radimer/ Cornell Hunger and Food Insecurity measures were used to assess food security status. Results: The information gathered from this study indicated that majority of households in this study were food insecure. The results show that 75% of the respondents interviewed were experiencing household food insecurity, whereas 58.3% having individual food insecurity and 48.8% with child hunger. Higher prevalence of household food insecurity was observed in the urban area. Meanwhile, individual food insecurity and child hunger were more prominent in the rural area. From the variables available in this study, household income, income per capita and coping strategies showed a significant associations with food security status (p<0.05). onclusions: The findings suggest that food insecurity among household in this study were primarily a direct result of inadequate income to buy sufficient foods for the household members. This further suggests why more households were found to rely on non-food related coping strategies in order to acquire enough foods to feed their family.